Effect of water absorption on the dynamic mechanical properties of composites used for windmill blades - Faguaga, Marcos Emmanuel (2012)
Glass fiber - unsaturated polyester composites (with and without nanofiller) were produced by using the VARI (vacuum assisted resin infusion) technique. These materials will be used in windmill blades and, therefore, they are expected to be exposure to high humidity environments. The fabricated specimens were immersed in water at 80 ºC for different periods of time. DMA (dynamic mechanical analysis) technique was employed to investigate the matrix degradation and interfacial debonding of the aged speci- mens. The gradually decreased Tg (glass transition temperature), Eo (storage modulus), and the increased tan delta (energy dissipation) with extended exposure time indicated that both the matrix and the interface had been deteriorated by the water. While matrix degradation occurs in a short period of time, composites degradation takes place gradually, showing that the degradation of the interphase in composites is the limiting step for the whole degradation process. Nanoclays were incorporated to the UP (unsaturated polyester) matrix showing a detrimental effect in degradation resistance, probably because of the degree of hydrophilicity of the selected clay, which produces a weak interphase with the polymeric matrix.